ANALISIS KANDUNGAN GIZI EKSTRAK KULIT SALAK PRODUKSI KELOMPOK TANI ABIAN SALAK DESA SIBETAN SEBAGAI UPAYA PENGEMBANGAN POTENSI PRODUK PANGAN LOKAL - dhyana putri (Meditory : The Journal of Medical Laboratory, 2016)
BackgroundSnakefruit more technically known as ‘Salak’ (Salacca sp) is native fruit of Indonesia regarded as exotic fruit that can consumed not only its flesh fruit but also its skin in the form of extract as it has an efficacy. Extract of snakefruit rind can be proceed into a healthy beverages that contains phenolic compounds which known as natural antioxidants. ObjectiveThis study aimed to describe the content of nutrients such as carbohydrates, proteins, and antioxidants in the extract of snakefruit rind products. This data will be useful as information material to local food industryas well as further research on the processed products for health. Methods This research is a descriptive study that examines the content of carbohydrates, protein, and antioxidants in the extract of snakefruit rind products. Samples were rind of snakefruit with various concentration masses, in water ratio 1%, 5%, 10%, and non compositions. ResultCarbohydrate, protein, antioxidant capacity and IC50 respectively for each composition, are (1) the composition of the 1%: -0.04%; 0.21%; 20.70 ppm, 426.58 ppm; (2) the composition of 5%: 0.82%; 0.20%; 73.40 ppm; 151.41 ppm; (3) the composition of 10%: 0.93%; 0.20%; 110.29 ppm; 87.11 ppm; (4) non composition: 28.14%; 44.90%; 215.10 ppm; 56.10 ppm, and non composition: 1.00%; 0.00%; 25.73 ppm; 92.18 ppm. The most potential nutrient compound in extract of snakefruit rind is the antioxidant, which produced as beverages like tea product. The composition of 10% is the most active category of antioxidant activity, whereas 5% in medium category, and composition of 1% in weak category. Carbohydrates and proteins compound are gradually lower in each composition, caused by boiling process due to the process of water dilution. ConclusionsThis study revealed that extract of snakefruit rind can produced as healthy beverages (such as tea), as it is a potential wastes treatment for local food products. The extract of snakefruit rind consist of nutrition just like proteins, carbohydrates which are great for health and also contains lots of a powerful antioxidant and works well to prevent cardiovascular disease, strokes, and even cancer, prevent allergies, increase fertility, and boost immunity. Keywords: Rind of snakefruit. Antioxidant, Tea